Polarization interferometer using Liquid Crystalline Polymer waveplate for wavelength measurement - Wierzba, Pawel; Mazikowski, Adam (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> Two-beam polarization interferometer for measurement of the change of the wavelength of a tunable semiconductor laser was designed built and tested. This interferometer uses a λ/8 waveplate made from Liquid Crystalline Polymer in order to generate two output signals in quadrature. The λ/8 waveplate can be manufactured either on a beamsplitter face or on the mirror surface, reducing the cost and complexity of the optomechnical assembly. Experiment results show that resolution of 2pm was attained for the wavelength range 628-635nm. The range of operation of such interferometer can be extended if wavelength-dependent Heydemann correction is used. Full Text: PDF References D. Mawet et al., "Optical Vectorial Vortex Coronagraphs using Liquid Crystal Polymers: theory, manufacturing and laboratory demonstration", Opt. Expr. 17, 1902 (2009), CrossRef G. Myhre et al., "Liquid crystal polymer full-stokes division of focal plane polarimeter", Opt. Expr. 20, 27393 (2012), CrossRef C. Maurer, A. Jesacher, S. Fürhapter, S. Bernet, M. Ritsch-Marte, "Upgrading a microscope with a spiral phase plate", J. Microscopy 230, 134 (2008), CrossRef P. Juncar, J. Pinard, "Instrument to measure wave numbers of cw and pulsed laser lines: The sigmameter", Rev. Sci. Ins. 53, 939 (1982), CrossRef P. Wierzba, M. Gnyba, "Liquid crystalline optical components for application in optical sensing", Eur. Phys. J. ST 154, 235 (2008), CrossRef P.L.M. Heydemann, "Determination and correction of quadrature fringe measurement errors in interferometers", Appl. Opt. 20, 3382 (1981), CrossRef